Проблеми правового регулювання реалізації трудових прав працівників за законодавством України - Остапенко, Ю. О. (My University, 2024)
Дисертацію присвячено з’ясуванню актуальних проблем правового регулювання реалізації трудових прав працівників за законодавством України та розробці теоретико-практичних пропозицій і рекомендацій щодо вирішення цих проблем. Обґрунтовано, що під час дослідження проблематики правового регулювання трудових прав працівників і змісту механізму реалізації таких прав потрібно використовувати комплекс методів наукового дослідження, який, зокрема, включає логіко-семантичний, формально-юридичний, історикоправовий, системно-структурний, статистичний, порівняльно-правовий та інші методи. Констатовано, що трудові права працівників є важливим комплексом прав людини, який дозволяє їй реалізувати свій трудовий потенціал, покращити якість життя, а отже, він виступає основою (гарантією) набуття та повноцінної реалізації працівником (у відповідній частині – його сім’єю) низки соціальних, культурних, громадянських, політичних та інших прав людини. Трудові права працівника являють собою систему, структуру якої утворюють дві основні групи прав: базові трудові права працівників (індивідуальні базові трудові права, колективні базові трудові права); спеціальні трудові права працівників (спеціальні статусні трудові права, спеціальні ситуативні трудові права). Доведено, що реалізація працівником його трудових прав є складним комплексним процесом приведення положень трудового законодавства, якими закріплено суб’єктивні права працівника, у дію (їх об’єктивації). Така реалізація прав працівника виражається у формах юридично значимої діяльності та повинна ґрунтуватись на нормах чинного законодавства, а також узгоджуватись із відповідним комплексом принципів. Розкрито багатоаспектну проблематику реалізації трудових прав працівників в умовах поширення нетипової зайнятості та похідного явища – прекаризації зайнятості. По-перше, нетипові форми зайнятості, що в тій чи іншій мірі врегульовані діючим законодавством про працю, розвиваються та трансформуються відповідно до потреб ринку, за темпами їх розвитку не встигає змінюватись трудове законодавство. По-друге, нетипова зайнятість включає значну кількість форм зайнятості, які не врегульовані законодавством або ж є такими, що на практиці сторонами цих відносин виступають особи, діяльність яких врегульована цивільним чи господарським законодавством. Особливу проблему складає те, що нетипова зайнятість переважно спрямовується на оптимізацію витрат роботодавця на трудовий ресурс за рахунок деформації та маргіналізації правового статусу працівників. У зв’язку із цим зазначені форми зайнятості є сумнівними та ризикованими в силу ефекту прекаризації зайнятості, вплив якої знижується залежно від посилення трудоправової форми забезпечення соціальної безпеки працівників та нормативно-правового забезпечення реалізації трудових прав. Встановлено, що комплексне удосконалення правового регулювання реалізації трудових прав працівників в Україні повинно орієнтуватись на цінності трудового права, а також здійснюватися у трьох напрямах. По-перше, необхідно розробити і прийняти Закон України «Про підвищення гарантій реалізації прав працівників», що передбачатиме такі зміни до КЗпП України: доповнення ст. 22 КЗпП України ч. 2-1, норми якої визначатимуть недотримання роботодавцем вимог частин 1 і 2 ст. 22 Кодексу в якості грубого порушення трудового законодавства; доповнення ст. 23 КЗпП України ч. 3, в якій передбачатиметься, що у випадках, коли трудовий договір було безпідставно укладено на визначений строк, він вважатиметься безстроковим. По-друге, розроблення та прийняття Закону України «Про внесення змін до КЗпП України щодо врегулювання нетипової зайнятості», яким буде: закріплено правило, відповідно до якого нетипові працівники володіють обсягом базових трудових прав і можливостями їх реалізації; уточнено особливості виконання надомної роботи членами сім’ї працівника; доповнено Кодекс главою «Нетипова зайнятість», яку складатимуть такі статті: «Особливості нетипової зайнятості», «Нетипові працівники», «Дистанційна робота», «Надомна робота», «Залучена форма зайнятості» та інші. По-третє, удосконалення правового регулювання у частині підвищення ролі судової практики в оптимізації функціонування правового механізму реалізації трудових прав працівників. The dissertation focuses on elucidating the current challenges in the legal regulation of the implementation of labor rights of workers under Ukrainian legislation. It aims to develop theoretical and practical proposals and recommendations for addressing these challenges. The study establishes that examining the issues of legal regulation of workers’ labor rights, and the content of the mechanism for implementing these rights, necessitates a comprehensive approach. This approach should employ a variety of scientific research methods. These methods include logical-semantic, formal-legal, historical-legal, system-structural, and statistical methods. Additionally, comparative-legal methods and other relevant techniques are also essential. The dissertation establishes that workers’ labor rights are a crucial component of the contemporary human rights complex. These rights enable an able-bodied person to realize their labor potential and improve their quality of life. Therefore, they act as a foundation or guarantee for workers (and, to an extent, their families) to acquire and fully exercise various social, cultural, civil, political, and other human rights. The structure of an employee’s labor rights is systemic, comprising two main groups. The first group is basic labor rights of workers, which includes personal basic labor rights and collective basic labor rights. The second group encompasses special labor rights of employees, divided into special status labor rights and special situational labor rights. The dissertation substantiates the position that an employee’s exercise of their labor rights should be viewed as a complex, integrated process. This process involves enacting the provisions of labor legislation that safeguard the employee’s subjective rights, a concept known as the objectification of legal norms. The implementation of these rights is manifested through forms of legally significant activities. Moreover, it must be grounded in the norms of current legislation. Additionally, this implementation should align with a corresponding set of principles. It has been determined that the proper exercise of labor rights by an employee is contingent upon at least five key conditions. First, the implementation of labor rights must align with the principle of legal certainty. Second, the exercise of labor rights should manifest in practice, free from undue obstacles posed by employers, colleagues, the workforce, society, and the state. Third, the exercise of labor rights implies that the worker can rely on certain guarantees. These guarantees should facilitate progress towards the desired objectives in labor and employment. Fourth, the exercise of labor rights entails that the employee, during or as a result of this process, receives the benefits inherent in the labor rights being exercised. These benefits should be to the appropriate extent and provided for by normative or contractual methods. Fifth, the implementation of labor rights must not involve the abuse of these rights. Therefore, the exercise of labor rights by an employee must respect the boundaries of proper use. These boundaries include moral and legal limits, as well as formal legal constraints. Adequate legal guarantees significantly aid the implementation of workers’ labor rights. The dissertation reveals the complex issues surrounding the implementation of workers’ labor rights in the context of the proliferation of atypical employment and its derivative phenomenon, precarization of employment. Firstly, atypical forms of employment, to varying extents governed by current labor legislation, are evolving rapidly to meet market demands. However, labor legislation struggles to keep pace with this rapid development. Secondly, atypical employment gives rise to many forms of employment that fall outside legal regulation or are such that in practice, parties resort to civil or economic legislation for governance. A particular concern is that atypical employment primarily seeks to optimize employer costs for labor resources. This optimization often leads to the deformation and marginalization of workers’ legal status. Consequently, these forms of employment are viewed as questionable and risky due to the effects of employment precarization. The impact of precarization ends to diminish with the strengthening of the labor legal form that ensures workers’ social security and legal support for the implementation of labor rights. It has been determined that a holistic enhancement of the legal regulation of labor rights implementation in Ukraine should adhere to the values of labor law. This improvement should be pursued in three key directions. Firstly, there is a need to develop and adopt the Law of Ukraine ‘On increasing guarantees for the implementation of workers’ rights.’ This law should introduce specific changes to the Labor Code of Ukraine. One such change includes the addition of part 2-1 to Article 22 of the Labor Code. This new part would classify an employer’s failure to meet the requirements of parts 1 and 2 of Article 22 as a serious violation of labor legislation. Another change involves supplementing Article 23 of the Labor Code with a new part 3. This addition would stipulate that if an employment contract is unjustifiably concluded for a fixed term, it should be considered as unlimited. Secondly, the development and adoption of the Law of Ukraine ‘On Amendments to the Labor Code of Ukraine to regulate atypical employment’ is proposed. This law aims to introduce several key changes. It will establish a rule specifying that atypical workers be entitled to a range of basic labor rights and have the capacity to exercise these rights. It will clarify the specifics of home work performed by members of the employee’s family. Additionally, the Labor Code will be augmented with a new chapter titled ‘Atypical Employment.’ This chapter will comprise articles such as ‘Features of Atypical Employment,’ ‘Atypical Workers,’ ‘Remote Work,’ ‘Homework,’ and ‘Involved Form of Employment,’ among others. Thirdly, there is a need for the improvement of legal regulation in terms of enhancing the role of judicial practice. This enhancement is vital for optimizing the functioning of the legal mechanism that facilitates the realization of labor rights for workers.
Problems of Legal Regulation of the Implementation of Labour Rights of Workers under Ukrainian Legislation
Keywords: проблеми правового регулювання; право; реалізація трудових прав